Aspectos clínicos, epidemiológicos e moleculares do papilomavírus genital em adolescentes gestantes - CAVALCANTE, José Carlos Wilkens (Universidade Federal do Pará, 2015)
Cervical cancer represents the third most common cancer in the world. Its etiologic agent is HPV. HPV is the most prevalent sexual transmissible disease in the world, affecting mostly young women. Adolescence is a time of behavioral, social and body changes, which reflects on the adolescent’s conscious awakening for sex, that can lead to contact with sexual transmissible diseases and early pregnancy. Being so, it is a time when the woman is more susceptible to infection, such as HPV. This project was dedicated to estimate the prevalence of HPV and to evaluate factors associated to this infection in pregnant adolescents in the Health Unique System, Pará State. It was a prospective transversal study including 257 pregnant women aging 12 to 19 attended at municipal (Curió and Tapanã) and state (Mother-child Reference Unit and Woman’s ambulatory of Holy House of Mercy of Pará Foundation Hospital) health units. The selected patients were submitted to a clinical-epidemiological questionnaire and to harvest of cervical-vaginal material for detection of DNA-HPV through polymerase chain reaction (PCR). The association of HPV infection and risk factors was evaluated through chi-square test (χ2) and/or Fisher’s exact test, with an alpha significance level of 0,05. HPV prevalence was 38.1% (98/257), affecting preferentially pregnant adolescents on the third gestational trimester (44.4%; p = 0.0312), between 11 and 14 years-old, with less than 6 years of schooling and those who did not have a mate. The risk factors associated to HPV infection in the population, also varied according to the gestational trimester, were “two or more sexual partners in life”, “first pregnancy” and “genital problems”. These findings show the adolescents susceptibility to HPV infection and, consequently, to the development of pre-neoplastic and malignant lesions. Therefore, there is the need of educational public measures in health promotion.